2021
DOI: 10.13057/biodiv/d220748
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Leaf architecture of 35 species of Dipterocarpaceae cultivated in Forest Area with Special Purposes in Carita, Banten, Indonesia

Abstract: Abstract. MeinataA, Na’iem M, Adriyanti DT, Syahbudin A. 2021. Short communication: Leaf architecture of 35 species of Dipterocarpaceae cultivated in Forest Area with Special Purposes in Carita, Banten, Indonesia. Biodiversitas 22: 2952-2960. Dipterocarpaceae is a major commercial timber characterized by high unbranched bole, paired stipules, and winged fruit. The identification process in the family becomes problematic, in cases where the generative organ is absent. Therefore, a new approach needs to be estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…As a photosynthetic organ, the leaf provides survivability for the plant, and this study showed that the variation in the progeny test of S. leprosula happens in certain characters only. This result strengthens the study that supports leaf architecture as a persistent character in a species (Meinata et al 2021). In conclusion, the S. leprosula showed leaf architecture variations as its response to their environment in four characters, namely laminar shape, apex shape, base shape and midrib thickness.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…As a photosynthetic organ, the leaf provides survivability for the plant, and this study showed that the variation in the progeny test of S. leprosula happens in certain characters only. This result strengthens the study that supports leaf architecture as a persistent character in a species (Meinata et al 2021). In conclusion, the S. leprosula showed leaf architecture variations as its response to their environment in four characters, namely laminar shape, apex shape, base shape and midrib thickness.…”
Section: Discussionsupporting
confidence: 89%
“…This has been proven to separate two different genera in Dipterocarpaceae, i.e. Hopea and Dryobalanops (Meinata et al 2021).…”
Section: Along With Genetic Factors (De Kort Et Al 2021)mentioning
confidence: 99%
See 1 more Smart Citation
“…Other morphological characters that are also proven to be used as distinguishing characters are the apex, vein, and basal. Leaf morphological characteristics of some plants showed that the measured apex, vein, and basal leaves showed significant differences, namely 35 species of dipterocarfaceae [28], local durian of Banten Province [29], vitex negundo [30], a vein of cinnamon cebuense [27], basal, and vein jujube [31], philippine apex [26], Hopea and Shorea species [27].…”
Section: B Leaf Angle Charactersmentioning
confidence: 99%